Analisis Dan Perancangan Sistem Informasi Pendaftaran Pelanggan Baru Dan Order Berbasis Web Pada PT. Dolphin S.I.C.M Tangerang - Tamzil, Fachmi (Lembaga Penerbitan Universitas Esa Unggul, 2008)
Computer technology updates unit process revolution in manual implementation to computer technology which called computerization. PT. DOLPHIN is a company which moving in chocolate industry which still use manual registration I’ll now. With this method, still find mistake with this method a mistake which always found is registration now customer process. Less product promotions and less promotion company promotions to customers. This all mistakes are the problem which can be affecting the company do not growth. Because of computerization registration system new customer and product order base on web can be a erectly solutions in solve PT. DOLPHIN problems for process new customer registrations. Analysis and constructions system with united modeling language and system which build program language PHP from result of this research, found a system between of data base system which conduction to help for set up customer file and customer order, so with this system can changed input system.Keywords: Information System, Customer Registration, Order